Integrating Livestock for Enhancing Sustainability of Soil, Water and Agroecosystem: Implications from a One Health Perspective - Md. Emran Hossain (International Journal of Sustainability, 2026)
Livestock systems play a pivotal role in sustaining environmental health, enhancing ecosystem services, and supporting agricultural productivity. Well-managed integration of livestock into agroecosystems contributes to soil fertility through organic matter deposition, microbial stimulation, and nutrient cycling, while improving soil structure and long-term productivity. Grazing and pasture management regulate water infiltration, retention, and hydrological balance, mitigating soil erosion and enhancing water-use efficiency. Livestock also promote biodiversity by maintaining habitat heterogeneity, facilitating coexistence with wildlife, and supporting plant and microbial diversity, thereby preserving ecosystem resilience. Furthermore, livestock contribute to carbon sequestration, biomass utilization, and renewable energy generation, reducing greenhouse gas emissions and advancing circular bioeconomy strategies. Despite these recognized benefits, knowledge gaps remain regarding the optimal integration of livestock to maximize environmental services while minimizing trade-offs. Quantitative assessments of livestock-mediated impacts on soil carbon stabilization, nutrient retention, water regulation, and biodiversity under varying agroecological conditions are limited. This review synthesizes current knowledge on the mechanisms through which livestock enhance soil, water, and biodiversity sustainability, highlighting the interplay between productivity and ecological conservation. Future research directions are proposed to optimize grazing management, improve nutrient and water efficiency, evaluate biodiversity outcomes, and integrate One Health principles, with an emphasis on climate resilience and sustainable land stewardship. Understanding these interactions is essential for designing adaptive livestock systems that balance agricultural productivity with environmental sustainability, ecosystem health, and global food security
Keywords: Agroecosystem; Biodiversity; Livestock; soil health; water regulation